Evaluation of dependency problems by projective tests; an overview - İkiz, T. T. (Journal of Dependence, 2008)
This review focuses on the problem of addiction and aims to explain the psychological processes of substance addicts through projective tests. While the term addiction, used in clinical psychopathology to describe a person's particular relationship with an object, may seem like self-destruction, users, on the contrary, describe it as a way to escape the stresses of daily life, find comfort, and alleviate anxiety. "Self-soothing processes," a key concept in psychoanalysis's approach to addiction, refer to the early problems of inadequate maternal imagery and identification in individuals who resort to "self-medication" with addictive substances. Projective tests, particularly the Rorschach test, which explore the psychodynamic aspect of personality, aim to examine the responses of these patients in two important addictions frequently encountered: alcohol and substance abuse, and to demonstrate which types of psychological processes are more important.
Keywords: dependence